Recovery of Oplopanax horridus (Sm.) Miq., an Important Ethnobotanical Resource, after Clearcut Logging in Northwestern British Columbia - Burton, Carla M.; Burton, Philip J. (Ethnobotany Research and Applications, 2015)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> The persistence and recovery of devil’s club (Oplopanax horridus (Sm.) Miq., Araliaceae) after clearcut logging in northwestern British Columbia, Canada, is investigated through a series of retrospective surveys. This species remains important to the traditional culture of many First Peoples of western North America and is being studied for its biological abilities by medical researchers. Based on observations in 16 clearcuts that had been logged 3 to 37 years earlier, it is clear that devil’s club can survive and grow in these disturbed habitats and appears to take at least 10 years for sizes to recover to those found in old-growth forests. The most successful populations of post-logging devil’s club probably escaped damage during logging operations, showed no recent signs of fire, and were associated with loose piles of dead branches, tree tops, and rotten logs. Consideration of these factors in forest management, in combination with the time since logging, should facilitate the resilience and sustainability of this species. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->